Catalytic co-pyrolysis palm oil empty fruit bunch and low-density polyethylene of plastic waste into high grade bio-oil. Issue 1 (February 2021) - Sunarno,; Zultiniar,; Santoso, A H; Utama, P S
Abstract: Bio-oil produced from biomass pyrolysis is still acidic and has a low heating value. Co-pyrolysis is a process of pyrolysis of biomass and material that has a higher (H/C) effective. Low-density polyethylene (LDPE) is a type of plastic waste that has a higher hydrogen index than empty fruit bunch (EFB). To improve the quality of bio-oil, it is necessary to co-pyrolysis EFB and LDPE using a calcium oxide catalyst. The purpose of this research is to produce bio-oil from a mixture of EFB and LDPE, to determine the effect of the CaO catalyst ratio and temperature on the bio-oil yield, and to determine the physical and chemical characteristics of the bio-oil product. The catalytic co-pyrolysis process uses 10 grams of EFB/LDPE mixture (EFB/LDPE ratio 50%:50%), CaO catalyst with a variation of CaO/raw material ratio (1%, 2%, 3%, 4%, and 5% w/w) and temperature variations (400°C, 450°C, 500°C, 550 and 600 °C), with nitrogen gas flowing at a flow rate of 400 mL/min for 45 minutes. The highest yield generated on the use of CaO/raw material ratio of 5% w/w and temperature of 550 °C was 35.2%. The characteristics of the bio-oil obtained were the density of 0.948 g/mL, the viscosity of 4.18 cSt, pH of 4.04, and heating value of 43.4 MJ/Kg. The results of GC-MS analysis showed that bio-oil contained 37.05% phenol compounds, 27.88% hydrocarbon, 20.27% ketones, 7.21% alcohol, 4.36% aldehydes, and 1.08% ester.